Class Clash: Unpacking Conflicts of Class Affiliation in the Bodily Practices of Polish Men Under 35 Years with Working-Class Origins - Anna Wójtewicz; Alicja Jaskulska; Łukasz Lutomski-Juryłowicz (Qualitative Sociology Review)
The article examines conflicts of class affiliation in the bodily practices of young Polish men of working-class origin. The empirical basis of the analysis is individual in-depth interviews with biographical elements carried out in 2022 as part of a study on the bodily practices of four generations of Polish men. The article contains the state of research on practices in the context of class affiliation. The theoretical framework is based on the concept of classist phantasm and middle-class hegemony. The study shows the critical importance of working-class backgrounds in shaping and controlling the body throughout the lifespan. The piggy bank ethos is one of the key categories emerging from the analysis, and research participants remain trapped in negotiating class identity reflected in bodily practices. In negotiating their class affiliation, men experience conflict with the values of the family of origin from their early teenage years. As they study and strive for advancement, they pay a hidden emotional cost, as they must authenticate themselves as deserving of their place in the middle class. Even if they are upgrading to the middle class (as working adults), they remain in the power of the piggy bank ethos. The study’s main conclusion is that social advancement is only partly achievable. Climbing up the social ladder, the study participants still balance middle-class practices and working-class values, which become apparent in what they do about the body.